2008
DOI: 10.2174/187152108785908866
|View full text |Cite
|
Sign up to set email alerts
|

Telbivudine for Chronic Hepatitis B. A Review

Abstract: Three hundred and fifty million people worldwide are estimated to be chronically infected with hepatitis B virus. 15%-40% of these subjects will develop cirrhosis, liver failure or hepatocellular carcinoma during their life. Approved drugs for chronic hepatitis B treatment include: standard interferon-alpha 2b, pegylated interferon-alpha 2a, lamivudine, adefovir dipivoxil, and entecavir. Unfortunately, these agents are not effective in all patients and are associated with distinct side effects. Interferons hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…LDT is an orally bioavailable L-nucleoside with potent and specific anti-HBV activity and has been proved to have better therapeutic responses and less virological resistance in CHB patients (25,29,30). Several studies have also shown that LDT inhibits HBV replication by modulating T cell immunity (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…LDT is an orally bioavailable L-nucleoside with potent and specific anti-HBV activity and has been proved to have better therapeutic responses and less virological resistance in CHB patients (25,29,30). Several studies have also shown that LDT inhibits HBV replication by modulating T cell immunity (20,21).…”
Section: Discussionmentioning
confidence: 99%